What to tell the family? Predisposition for hereditary childhood cancer (Research, Society and Development, 2020)
Objective: Identify the knowledge of family members about childhood disease with a hereditary predisposition to cancer and analyze how information about the disease is disseminated in the intrafamily scenario. Methodology: Qualitative, exploratory research. Data collection was carried out with 16 family members of children enrolled in the genetic counseling clinic, through individual, semi-structured interviews with thematic analysis. Results: The lack of knowledge about the disease with a hereditary predisposition was present in the family members' discourse. Some communication strategies developed by family members for the child and distant family members were identified. The information obtained in genetic counseling influenced the identification of family members of hereditary risk and care with future generations. Conclusions and implications for the practice: Communication was present in the family environment with the child and family members facing the disease with a hereditary predisposition to cancer. Health professionals need to be trained in the field of genetic oncology to contribute to the identification of affected children and families. The information acquired at the genetic counseling clinic contributes to the tracking of family cases, dissemination of information and the quality of life of those affected.